Treating early-stage centrally-located non-small cell lung cancer with DCAT-SBRT in centers lacking the VMAT technique: a comprehensive study - Huang, Yangyang; Yang, Jun; Song, Rui; Qin, Tingting; Yang, Menglin; Liu, Yibao (Frontiers in Oncology, 2024)
BackgroundVolumetric-modulated arc therapy (VMAT) may have the highest overall performance for stereotactic body radiotherapy (SBRT) treatment of inoperable early-stage NSCLC. However, in centers lacking the VMAT technique, the dynamic conformal arc therapy (DCAT) technique is potentially the best option for small and rounded NSCLC-SBRT. Therefore, we will comprehensively analyze the advantages of the DCAT versus the other techniques except VMAT in terms of dosimetry, plan complexity, delivery time, γ-passing rates and the interplay effect.Methods36 patients with early-stage centrally located NSCLC with PTV volumes < 65 cc were enrolled. All patients were redesigned with 50Gy/5f, and 100% of the prescribed dose was normalized to cover 95% of the PTV. The other two delivery techniques compared to the DCAT technique include 3-dimensional conformal radiotherapy (3DCRT) and intensity-modulated radiotherapy (IMRT), which use the same parameters for all three techniques.ResultsThe dosimetric parameters of the 3-group plans all met the RTOG 0813 protocol. Unsurprisingly, plan complexity parameters such as segments and MUs were significantly reduced in the DCAT plans by 159.56 and 925.90 compared to the IMRT plans, respectively (all P < 0.001). The delivery time of the DCAT plans was the least of 164.51 s (all P < 0.05). Compared to the IMRT plans, the γ-passing rates were higher in the DCAT plans (P < 0.001), with the most significant difference of 6.01% in the (2%, 1 mm) criteria. As for the interplay effect, the mean dose difference (MDD) in the DCAT plans was as good as the 3DCRT plans at different respiratory amplitudes but better than the IMRT plans (all P < 0.05), and the MDD of DCAT plans did not exceed 3% in all respiratory amplitude.ConclusionIn centers lacking the VMAT technique, implementing SBRT treatment based on the DCAT technique for inoperable early-stage centrally-located NSCLC patients with PTV volumes < 65 cc achieves better treatment efficiency and delivery accuracy while maintaining the plan quality.